Patient-centered enterostomal therapy as a shared management strategy and clinical decision (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Care arises with the history of humanity, is the object of nursing work and has been studied by philosophers, historians and anthropologists, but it is nursing itself that produces more knowledge on the subject.
Keywords: Stomatherapy; Management; Nursing